A New Natural Language Processing-Based Essay Grading Algorithm - S. Suman Rajest; R. Regin; Shynu T; Steffi. R (International Journal on Integrated Education, 2023)
The evaluation of an English essay is one of the most significant and difficult activities that is manually carried out by knowledgeable and capable instructors and faculty members. The advancement of science and technology has made it possible to automatically evaluate an English essay by employing techniques pertaining to natural language processing. For any given English essay, the intelligent system provides a generic evaluation as well as the topic/question correlation. This evaluation is based on the NLP multiple neural network model, which was used to build the system. The evaluation of essays according to worldwide standards is the primary contribution of this innovation. Any worldwide grading system, such as the Graduate Record Examination, the International English Language Testing System, etc., is qualified to make use of the grading standard. The algorithm gives users the opportunity to test their knowledge on a range of criteria, from the most basic to the most complicated, that are included in the scoring of an English essay.